Miniaturized Circularly Polarized Stacked Patch Antenna on Reactive Impedance Surface for Dual-Band ISM and WiMAX Applications - Kush Agarwal; Saugata Dutta (International Journal of Antennas and Propagation)
This paper proposes a compact microstrip patch antenna for operating in 2.4 GHz ISM and 3.5 GHz WiMAX bands with circularly polarized (CP) radiation. The CP radiation in dual-bands is a result of two multilayered truncated corner stacked square patches, while the reactive impedance surface (RIS) is used for antenna size miniaturization for the lower operating frequency band. Since the overall lateral antenna dimensions are controlled by the lower frequency band (higher wavelength), reducing the electrical size of the antenna for lower band results in overall smaller antenna dimensions. The measured 3-dB axial ratio bandwidths of the in-house fabricated antenna prototype are 6.1% (2.40–2.55 GHz) for the lower band and 5.7% (3.40–3.60 GHz) for the upper band, while the 10-dB S11 bandwidths for the two bands are 8.1% (2.39–2.59 GHz) and 6.9% (3.38–3.62 GHz), respectively. The maximum gain at boresight for the lower band is 2.93 dBic at 2.5 GHz, while the gain for the upper band is 6.26 dBic at 3.52 GHz. The overall volume of the proposed antenna is 0.292λo × 0.292λo × 0.044λo, where λo is the corresponding free-space wavelength at 2.5 GHz.